Analysis of subnational CO2 mitigation policy pressure in the residential sector in China. (15th April 2021) - Meng, Fanxin; Chen, Siyi; Cheng, Shulei; Chen, Boyang; Li, Zhiwen; Wang, Feiran; Liu, Gengyuan
Abstract: Evaluating CO2 mitigation policy pressure in the residential sector is key to effectively taking CO2 mitigation actions. By developing the carbon emissions reduction index (CERI) and applying the refined Laspeyres technique, this study qualified the Chinese residential CO2 mitigation policy pressure in 29 provinces and 286 cities from 2005 to 2015. The results showed that, although the average CO2 mitigation policy pressure in the residential sector showed a rise trend both at the provincial level and at the city level, the average CERI value and growth rate of the former was larger than the latter. Meanwhile, the CO2 mitigation policy pressure in the residential sector was both quite different with provinces and cities. Moreover, CO2 intensity contributed the most to the changes in the average CERI at the provincial level, while the main driver of the changes in the average CERI was CO2 inequality at the city level.